Profile of Students Creative Thinking Skills and Implementation of Inquiry-based Learning Assisted by Physics 3D Module - Nisa, Nabillah Zuhrotun; Prahani, Binar Kurnia; Marianus; Irwanto; Kurtulus, Muhammed Akif; Hudha, Muhammad Nur (Jurnal Pedagogi dan Pembelajaran, 2024)
So far in physics subjects, especially material that contain many formulas, students have complained about difficulties in accepting the material. This is because the learning model and learning media used are still not in accordance with the material provided. The study aimed to analyze surveys about learning model used in physics lesson and tests using indicators of creative thinking ability specially on the material elasticity. This research is preliminary research with a descriptive research design. This research does not use a hypothetical test design but rather a description research project. The study was conducted on 181 students consisting of: 78 male students and 103 female students. The study uses three instruments to gather data, i.e. a.) a creative thinking test instrument of four indicators flexibility, elaboration, originality and fluency on material elasticity and Hooke law, b.) teacher interview sheet about learning model used in physics lesson, c.) student questionnaire about perspective of physics lesson, learning models and learning media. The results showed the creative thinking ability of students still belongs to the low category. The implication is that teachers must be able to apply appropriate learning models and learning media in the process so that students are able to receive the material well and have the ability to think creatively.